Explaining gaps in educational transitions between migrant and native school leavers - Markus Zimmermann (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2019)
This paper analyzes the reasons for the large and persistent gaps in transitions after secondary school between native pupils compared to second- and third generation immigrant pupils in Germany. I first document that differences in parental background, skills (such as school degrees or test scores), and school fixed effects explain part of the migrant-native gaps, but are not sufficient. Conditional on these factors, there is a "polarization" of educational choices: migrants are more likely to attend tertiary education, less likely to attend vocational education, and more likely to end without qualified training than their background and skills would predict. I then show that this polarization is driven by the migrant pupils' more academically oriented career aspirations and expectations before leaving school. On the one hand, these higher ambitions allow higher skilled migrants to hieventertiary education despite their less favourable background characteristics. On the other hand, less skilled migrants who in Germany's tracked school system do not have the option to enter academic education, may be diverted from vocational training as a more viable alternative. These patterns are stronger for boys than for girls. Finally, I discuss various possible explanations for the migrants' different career plans, including expected labour market returns to education, expected discrimination, the intention to leave Germany, overconfidence, or information deficits.
Keywords: I24; I21; J24; J15; 330; migrant youth; vocational education; tertiary education; aspirations; expectations